Handicap cognitif et agression sexuelle : (Re)penser la capacité à consentir - Michèle Diotte (Genre, Sexualité et Société)
As part of this article, we wish to highlight the legal discourses and legal practices linked to the construct of the ability of people considered as « cognitively disable » to consent. This research includes four judgments given by the Court of Quebec as well as Ontario’s Court of Appeal. These judgments concern accusations of sexual assault on women considered as cisgender and as « cognitively disable ». This study explores the way Canadian Criminal Justice System analyses the capacity to consent in interaction with the cognitive dis/ability. While these few cases bring to light the importance given to the biomedical perspective in the determination of sexual consent capacity, we propose this evaluation be based on an understanding of the notion of choice.